First-principles calculations on the interfacial stability and bonding properties of HfN(111)/HfB2(0001) interface. (January 2023) - Yang, Tianxing; Han, Xiujun; Li, Wei; Chen, Xiaohong; Liu, Ping
Abstract: The interfacial stability and bonding nature of HfN(111)/HfB2 (0001) interface were studied by first-principles method. Twelve interfaces with different terminations (Hf- and N-terminated HfN(111) surfaces and B- and Hf-terminated HfB2 (0001) surfaces) and stacking sequences (top, bridge and center) were constructed. The four bridge site interfaces will finally transfer to the center-like one, indicating they are not stable. The Hf-B-cen interface has the best stability due to the smallest interfacial energy (−0.60 J/m 2 ) under B-rich condition and largest Wad (6.33 J/m 2 ), which theoretically proves that with the existence of excess B elements in the HfB2 layer, the best mechanical properties were obtained with modulation period of 150 nm for the HfN/HfB2 multilayer. And the bonding nature at the Hf-B-cen interface is covalent with ionic which can be attribute to the hybridization of the interfacial Hf-d in HfN(111) and B-p in HfB2 (0001). Highlights: Twelve HfN(111)/HfB2(0001) interfaces were studied with first-principles calculations. The Hf-B-cen interface is the most stable one. The four bridge site interfaces will finally transfer to center-like ones. He Hf-B-cen interface exhibits covalent with ionic bonding feature.